Extraction of patchouli oil using steam distillation - Dewi Haryani, Sulaiman (2008)
This study is about Extraction of Patchouli Oil Using Steam Distillation. The objective of this research is to study the feasibility of the optimum condition of steam distillation in patchouli oil extraction process. Patchouli oil extraction is still new but has gained large market demand for the benefit on therapeutic and healing properties of this essential oil. However, cost-effective route have yet to be develop. This research has identified two scope of study to achieve the objective which is to vary the effect of different extraction time and sample mass on the yields. In this extraction, part of the plant used is the leaves and stick. Firstly, the raw material is exposed 3 hours under direct sunlight and 3 days in room temperature. Dried patchouli plants are then cut to 2 cm in size. Then, the leaves are stacked in the extraction vessel. High pressured steam passed through the plant material from the bottom of the vessel. Hot steam will force open the pocket in which the essential oil of the patchouli was kept. Next, the steam which contains the essential oil passed through cooling system to condense the steam which would separate the essential oil from water. Pure oil is extracted with this method. For this equipment with the range of 7 hours extraction time and 2 kg to 4 kg sample masses, the optimum extraction time is at 7 hours with 3 kg sample mass.-Author